A systematic review of file sharing in mobile devices using peer-to-peer systems - Yasin, Waheed; Ibrahim, Hamidah; Abdul Hamid, Nor Asila Wati; Udzir, Nur Izura (Canadian Center of Science and Education, 2011)
Deployment of file sharing systems on wireless networks introduces several challenges specially when mobility comes into view. Thus, many researches have been performed in this field. The aim of this paper is to perform a systematic review on the existing solutions for file sharing in mobile devices based on Peer-to-Peer or shortly P2P approach. Five approaches are presented that are based on unstructured P2P systems; structured P2P system; mobile-to-mobile technique; tree-structured based; and incentive. These approaches of file sharing can work on one of the two wireless network configurations which are Mobile Ad Hoc Network (MANET) and infrastructure based network. Furthermore, we discussed the advantages and limitations of these approaches. Finally, this paper concludes with some insights for research directions in this area.